2016
DOI: 10.18805/lr.v0i0.7647
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new fertility restorers for development of early maturing pigeonpea hybrids

Abstract: The paper reports the identification of two early maturing fertility restorers viz.ICPR 2433 and ICPR 2438. The fertility restoration was found to be under the control of two duplicate dominant genes. Multi-location evaluation of the hybrids involving these restorers revealed that the fertility restoration of the hybrids was stable across seven environments. On average, the two hybrids (ICPH 2348 and ICPH 2433) out-yielded the control ICPL 88039 by a margin of over 100%. These results showed that with targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, the inheritance of fertility restoration is independent of the source of male sterility system. The gene action is unique to every individual CGMS system and was reported by Lay and Saxena (2011), Sawargaonkar et al (2012), Choudhary and Singh (2015), Saroj et al (2015), Sultana and Saxena (2017) and Saxena et al (2018) in pigeonpea. On comparison of the three methods utilized to assess the fertile and sterile plants, all the three methods showed same results for inheritance of fertility restoration.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the inheritance of fertility restoration is independent of the source of male sterility system. The gene action is unique to every individual CGMS system and was reported by Lay and Saxena (2011), Sawargaonkar et al (2012), Choudhary and Singh (2015), Saroj et al (2015), Sultana and Saxena (2017) and Saxena et al (2018) in pigeonpea. On comparison of the three methods utilized to assess the fertile and sterile plants, all the three methods showed same results for inheritance of fertility restoration.…”
Section: Discussionmentioning
confidence: 82%
“…(a) Plants with uniform sized, stained, large pollen grain and pollen fertility above 80% (Type A); (b) plants with stained and mixture of large and small sized pollen grains as in the F 1 hybrids and pollen fertility above 80% (Type B); and (c) plants with unstained shrivelled pollen grains and 100% pollen sterility (Type C) [Color figure can be viewed at wileyonlinelibrary.com] confirmed that fertility restoration is controlled by single dominant gene.The conclusive evidence from the assessment of segregating population involving the crosses, namely, CORG 990047A Â AK 261322, CORG 990052A Â AK 261322 and CORG 7A Â AK 261322, based on anther colour, pollen grain fertility and pollen grain morphology and staining proved that the inheritance of fertility restoration was controlled by single dominant gene. However, the inheritance of fertility restoration is independent of the source of male sterility system.The gene action is unique to every individual CGMS system and was reported byLay and Saxena (2011), Sawargaonkar et al (2012),Choudhary and Singh (2015),Saroj et al (2015),Sultana and Saxena (2017) andSaxena et al (2018) in pigeonpea. On comparison of the three methods utilized to assess the fertile and sterile plants, all the three methods showed same results for inheritance of fertility restoration.…”
mentioning
confidence: 84%